Evaluation of the mechanical properties and clinical efficacy of biphasic calcium phosphate-added collagen membrane in ridge preservation - Lee, Jung-Tae (J Periodontal Implant Sci, 2020)
PURPOSE: This study aimed to evaluate the biocompatibility and the mechanical properties of ultraviolet (UV) cross-linked and biphasic calcium phosphate (BCP)-added collagen membranes and to compare the clinical results of ridge preservation to those obtained using chemically cross-linked collagen membranes. METHODS: The study comprised an in vitro test and a clinical trial for membrane evaluation. BCP-added collagen membranes with UV cross-linking were prepared. In the in vitro test, scanning electron microscopy, a collagenase assay, and a tensile strength test were performed. The clinical trial involved 14 patients undergoing a ridge preservation procedure. All participants were randomly divided into the test group, which received UV cross-linked membranes (n=7), and the control group, which received chemically cross-linked membranes (n=7). BCP bone substitutes were used for both the test group and the control group. Cone-beam computed tomography (CBCT) scans were performed and alginate impressions were taken 1 week and 3 months after surgery. The casts were scanned via an optical scanner to measure the volumetric changes. The results were analyzed using the nonparametric Mann-Whitney U test. RESULTS: The fastest degradation rate was found in the collagen membranes without the addition of BCP. The highest enzyme resistance and the highest tensile strength were found when the collagen-to-BCP ratio was 1:1. There was no significant difference in dimensional changes in the 3-dimensional modeling or CBCT scans between the test and control groups in the clinical trial (P>0.05). CONCLUSIONS: The addition of BCP and UV cross-linking improved the biocompatibility and the mechanical strength of the membranes. Within the limits of the clinical trial, the sites grafted using BCP in combination with UV cross-linked and BCP-added collagen membranes (test group) did not show any statistically significant difference in terms of dimensional change compared with the control group.